Prehospital Airway Management Training and Education: An NAEMSP Position Statement and Resource Document. (4th January 2022) - Dorsett, Maia; Panchal, Ashish R.; Stephens, Christopher; Farcas, Andra; Leggio, William; Galton, Christopher; Tripp, Rickquel; Grawey, Tom
Abstract : Airway management competency extends beyond technical skills to encompass a comprehensive approach to optimize patient outcomes. Initial and continuing education for airway management must therefore extend beyond a narrow focus on psychomotor skills and task completion to include appreciation of underlying pathophysiology, clinical judgment, and higher-order decision making. NAEMSP recommends: Active engagement in deliberate practice should be the guiding approach for developing and maintaining competence in airway management. EMS learners and clinicians must be educated in an escalating approach to airway management, where basic airway maneuvers form the central focus. Educational activities should extend beyond fundamental knowledge to focus on the development of clinical judgment. Optimization of patient outcomes should be valued over performance of individual airway management skills. Credentialing and continuing education activities in airway management are essential to advance clinicians beyond entry-level competency. Initial and continuing education programs should be responsive to advances in the evidence base and maintain adaptability to re-assess content and expected outcomes on a continual basis.